Trajetórias do olhar: pintura naїf e história na arte paraibana - Costa, Robson Xavier da (2007)
The purpose of the present work is to emphasize the thematic aspects of the relationship between History and Art-naïf in Paraiba, involving the second half of the 20Th century. The work is based on analysis of the works of four living artists from Paraiba Alexandre Filho, Tadeu Lira, Isa Galindo and Analice Uchôa each one of them representing one of the following decades, studied respectively: 1960 s, 1970 s 1980 s and 1990 s. The goal of the research is to comprehend the main features that constitute this kind of artistic proposal, taking into account its syntax, its morphology, and its anthropological aspects, as well as the artistic and historical elements stemming from the relationship between the artists biographies and the making of their artistic work. The research also discusses possible ways of studying the Art-naïf as a historiography source from an analysis of the images provided by these artists who have been both nationally and internationally acclaimed. The present research is based on a broad cultural historical context, establishing a dialogue between the oral history, present time history, visual history and the history of everyday life considering the possible connections between the anthropology of the image and the science of the imaginary. At the outcome of this work, one can infer that Art-naïf is a visual poetic consolidated in our contemporary world, giving, at the same time, no sign of being diminished as one can see by observing the steady production of living artists and that of the new generation. The Paraiba Art-naïf integrated itself within the Modern Brazilian visual production, maintaining constant relationship with present-day signs, influencing and being influenced by the ever so frequent inter-cultural dialogues provided by Contemporary Art.